2022
DOI: 10.3390/jpm12040628
|View full text |Cite
|
Sign up to set email alerts
|

Improved Atrial Differentiation of Human Pluripotent Stem Cells by Activation of Retinoic Acid Receptor Alpha (RARα)

Abstract: Human pluripotent stem cell (hPSC)-derived cardiomyocytes have proven valuable for modeling disease and as a drug screening platform. Here, we depict an optimized protocol for the directed differentiation of hPSCs toward cardiomyocytes with an atrial identity by modulating the retinoic acid signaling cascade in spin embryoid bodies. The crucial steps of the protocol, including hPSC maintenance, embryoid body (EB) differentiation, the induction of cardiac mesoderm, direction toward the atrial phenotype, as well… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…S1A). We and others showed previously that RA redirects differentiation towards aCMs (Devalla et al, 2015; Schwach et al, 2017, 2022; Zhang et al, 2010), which occurs at high efficiency as evaluated by fluorescence activated cell sorting (Supplementary Fig. S1B).…”
Section: Resultsmentioning
confidence: 59%
See 2 more Smart Citations
“…S1A). We and others showed previously that RA redirects differentiation towards aCMs (Devalla et al, 2015; Schwach et al, 2017, 2022; Zhang et al, 2010), which occurs at high efficiency as evaluated by fluorescence activated cell sorting (Supplementary Fig. S1B).…”
Section: Resultsmentioning
confidence: 59%
“…Differentiation of hPSCs to ventricular or atrial EBs was performed as previously described (Schwach et al, 2022). Briefly, hPSC were seeded and aggregated in EB formation medium (Essential 8 containing 400 µg/mL Poly (vinil alcohol) (Sigma Aldrich, P8136) and 10 µM Y-27632 (Bio-Connect, S1049)) one day before starting the differentiation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RArγ transcripts are specifically detected in the endocardial cushion tissue and large developing vessels [ 70 ]. Moreover, RArα activation seems to improve the atrial differentiation of hiPSCs [ 74 ]. In this way, FGF signaling, which is known to sustain ventricular development, was inhibited.…”
Section: Protocols To Differentiate Hipsc-pmsmentioning
confidence: 99%
“…Future advancements in experimental methodologies, clinical imaging modalities, computational performance, standardization, and the need for clinical evidence to support the routine use of computational models in AFib management will help move this technology forward [ 105 ]. For that, the generation of hPSC-derived atrial cardiomyocytes [ 106 , 107 , 108 ] and the development of atrial tissues [ 109 , 110 , 111 ] have indicated the potential to model AFib in vitro and open new possibilities to generate robust datasets that facilitate in silico modeling.…”
Section: Models Of Afibmentioning
confidence: 99%